Achieving safe, smart & sustainable bridges : 2010 Concrete Bridge Conference : proceedings, february 24-26, 2010 Phoenix, Arizona (National Concrete Bridge Council, 2010)
Sumario: Contiene texto concerniente a la construcción de puentes para ingenieros y especialistas.